Digital, localised and human-centred design makerspaces: nurturing skills, values and global citizenship for sustainability - Ikram Sellami; Hira Amin; Ozcan Ozturk; Alina Zaman; Seda Duygu Sever; Evren Tok (Discover Education)
Abstract Maker Majlis, based in Qatar, was the first manifestation of a localised human-centred design makerspace in the Arabian Gulf region that went digital during the COVID-19 pandemic. It was a coalescence of three broad ideas: human-centred design thinking, sustainability and Islamic values. The digital makerspace hosted 229 participants from 25 countries. This paper aims to outline this platform and its programs and preliminarily assess their capacity to develop twenty-first century skills based on participants’ survey results of their learning experience. In doing so it also explores more broadly the role of informal digital makerspaces as a non-traditional educational approach in education for sustainable development. Overall, the findings indicate multifaceted positive benefits of these programmes on participants’ learning experiences, citizenship values, personal development, and holistic growth with ethical and social values. The participants valued the human-centered design and mentoring aspects of the programs for enhancing creativity, critical thinking, and problem-solving skills. Moreover, the programs promoted global citizenship by enabling collaboration across different backgrounds, and nurturing qualities such as confidence, self-respect, and respect for others. This research underscores the potential of digital makerspaces to serve as innovative educational models that support lifelong learning as well as the implementation of digital civics pedagogy.